Processos educativos: experiências de famílias em fase de remissão do câncer - Oliveira, Silvana Faraco de (2014)
The diagnosis and experiences of the treatment and follow up of a child or teenager with cancer can be a striking and destructuring not only for the patient but as well as the family. The emotional involvement of these families in this journey affects their own lives, since the experiences with cancer involve an adaptive process due to the troubles and changes that occur in the family dynamic, therefor, the family members learn how to deal with these difficulties to which they are exposed to and start to develop tackling strategies that allow them to adapt and survive in this new reality. In this context, the present research has as goals to identify the educational processes that occur in the living with cancer and understand how the families deal with the different phases related to the period of discovery, treatment and seeking for a cure for their children, brothers or sisters. A study case was developed in the qualitative nature and we counted with the collaboration of two families in which there was one child and one teenager in the follow up phase of cancer. The data gathering occurred in the city of São João da Boa Vista SP between the months of February and May of 2013, with open and individual interviews. The data analysis was made based on two themed categories: Resilience on cancer: A new meaning to life and Learning how to fight for life . The results revealed the after they have overcome the treatment phase, the families had a new meaning to the cancer experience, it was not seen as a synonym of death and punishment anymore and started to be seen as an opportunity of growth of everybody as human beings, which means that, the families understood that the experiences since the diagnoses and the treatment of cancer enabled them to think over their attitudes and forms of being in the world. In a general sense, all of them consider that the see and live life differently, they have become more comprehensive and less selfish, they are now concerned more with others, they cease the day and also they don t give as much importance to money and can now enjoy more the moments with their families. The collaborators of the research learned how to accept the cancer, have faith, trust and hope, not focusing on the disease, giving warmth and love to their children and siblings, to value the knowledge and feelings of the child, to follow the doctor s orientations, to exchange experiences with other people that have been through similar problems, to respect and seek the comprehension and union of all the family members and how to live intensely today. The appointed dimensions can contribute to the deconstruction of the stigma and the negative expectations the characterize cancer as a synonym of death, increasing hope and trust in the healing possibility and can be of special interest to think over the practice of health professionals, leading them to realize the importance of looking also to the families of the oncological patient, including them in care, respecting their feelings, knowledge, culture and forms of being and thinking, to accept and stand by them, consolidating with this the assistance giving of a humanized health care.